Genetic diversity and structure of Brycon henni in regulated and non-regulated water flow rivers of the Colombian Andes - Herrera-Pérez, J.; Jiménez-Segura, L. F.; Márquez, E. J.; Campo, O.; Soto-Calderón, I. D. (Frontiers in Environmental Science, 2023)
Abstract The sabaleta, Brycon henni, is a medium-size fish species found in the Andean range of the Magdalena-Cauca river basin in Colombia, where it is a fishery resource. Recruitment of sabaleta has affected construction of dams with unknown consequences on its genetic diversity and structure. Understanding the current genetic architecture in the dam-influenced areas compared to non-regulated water flow systems is crucial to diagnose the impact of human interventions and formulate proper management strategies. In this study, we evaluated the genetic structure and diversity of B. henni by using a set of microsatellites in individuals from 14 localities to identify the number of distinct genetic pools. We used various approaches to compare populations between regulated and non-regulated areas in the Magdalena-Cauca basin, and identified eleven well-differentiated and highly diverse population groups with marked genetic structures at local and regional levels. Genetic diversity of B. henni was very similar among non-regulated and dam-regulated water flow areas; however, one of the populations in non-regulated areas showed evidence of a founder effect associated with recent introductions. The effect of dams on the genetic structure of B. henni in the Magdalena-Cauca basin was negligible, probably due to their recent construction. Future reduction of genetic diversity and the loss of unique populations is expected due to the combined effect of geographic isolation and population declines. Thus, monitoring programs are necessary to detect changes in the genetic structure of fish populations to develop useful conservation actions.